2021
DOI: 10.1002/ehf2.13206
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of lung ultrasound in patients hospitalized for heart disease irrespective of symptoms and ejection fraction

Abstract: Aims Lung ultrasound B-lines are the sonographic sign of pulmonary congestion and can be used in the differential diagnosis of dyspnoea to rule in or rule out acute heart failure (AHF). Our aim was to assess the prognostic value of B-lines, integrated with echocardiography, in patients admitted to a cardiology department, independently of the initial clinical presentation, thus in patients with and without AHF, and in AHF with reduced and preserved ejection fraction (HFrEF and HFpEF). Methods and resultsWe enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Based on personal experiences and results of previous trials, we think that the number of USBLs can be used as a surrogate marker of cardiovascular risk and a predictor of outcomes in KTRs as well. Its diagnostic, therapeutic, and prognostic value has been demonstrated in acute and chronic heart failure [5,[36][37][38][39][40] with USBLs > 15 as a cut-off value for a poor outcome. In our cohort, moderate congestion (> 15 USBLs) was found only in six (3.8%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on personal experiences and results of previous trials, we think that the number of USBLs can be used as a surrogate marker of cardiovascular risk and a predictor of outcomes in KTRs as well. Its diagnostic, therapeutic, and prognostic value has been demonstrated in acute and chronic heart failure [5,[36][37][38][39][40] with USBLs > 15 as a cut-off value for a poor outcome. In our cohort, moderate congestion (> 15 USBLs) was found only in six (3.8%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…Another study with pre-discharge HF patients confirmed this cut-off irrespective of EF (29), which correlates with our findings since the best cut-off value was at 16 B lines in our cohort. B-lines also have an exceptional prognostic value, shown in patients with HF (19)(20)(21)(29)(30)(31). After a 1-year follow-up in dyspneic patients, an increased number of B-lines was associated with a higher hospitalization rate with a best cut-off at 6 B-lines (8 sector LUS) (32).…”
Section: Discussionmentioning
confidence: 99%
“…The number of B-lines is related to pulmonary capillary wedge pressure ( 16 ), NT-proBNP ( 17 ), and E/e′ in HF patients ( 18 ). LUS has a prognostic value in acute HF irrespective of EF ( 19 ) and chronic HF regardless of EF ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that B-profiles identified using lung ultrasound were more accurate for detecting cardiogenic causes of dyspnea than pleural effusion and TTE (41)(42)(43). The AHF Group of the European Society of Cardiology has stated that for patients with dyspnea and shock, lung ultrasound can be easily and rapidly interpreted, and it is necessary to perform lung ultrasound, in addition to transthoracic echocardiography, in an emergent setting for patients with suspected acute heart failure (44).…”
Section: Additive Value Of Lung Ultrasoundmentioning
confidence: 99%